Correlation between goal orientation and attitudes of Brazilian elite swimmers - Amaro, Leticia Alves; Prado, Paulo Augusto; Paiano, Rone; Verardi, Carlos Eduardo Lopes [UNESP]; Larizzatti, Marcos Fernando; Hirota, Vinicius Barroso (My University, 2017)
The aim of this study was to correlate motivation and attitudes towards sports competition of Brazilian elite swimmers. Through a correlational study we apply a scale of motivation and a scale of attitudes towards sports competition (TEOSQ and EAA) in 29 elite athletes (12 men and 17 women), Brazilian´s swimmers aged between 19 and 24 years (average age of the athletes is 21.48±1.42 years, 6.65% coefficient of variation); the statistic treatment included the calculation of Cronbach's alpha coefficient, descriptive statistics instruments, Spearman correlation and Mann-Whitney test (p≤0.05). The results showed a predominance related motivational orientation task of all swimmers and positive attitudes towards sporting competition, i.e., the extent that negative attitude tends to decrease, the positive increases, showing a negative correlation, strong and significant, and for the motivational orientation as it increases the orientation task also increases to the ego, significantly. We conclude that athletes like and enjoy competing and has characteristics of self-overcome being intrinsically motivated.
Keywords: Attitudes; Elite athletes; Evaluation; Motivation; Swimming